Estado nutricional, ingestão alimentar e marcadores séricos de cobre, manganês e zinco de pacientes com quelóide - Bersch-Ferreira, Ângela Cristine [UNIFESP] (2010)
Introduction: Studies on nutrition and keloid discuss the intake of macroand micronutrients. Regarding micronutrients, although the literature has already determined the association between trace elements and wound healing, studies about the relationship between them and the development of keloid are reduced. Objective: To investigate the nutritional status of patients with keloid, in relation to copper, manganese and zinc. Methods: 111 patients from the outpatient clinic of the Department of Pathological Scars of Plastic Surgery, UNIFESP were interviewed. Sixty-one belonged to keloid group (GQ) and 50 to control group (GC). Firstly, the body mass index (BMI) and percentage’s body fat (%Fat) were determined. Secondly, the dietary assessment was performed by the recall of 24 hours and 3 days of food records. After that, the patients were sent to the laboratory of the Association for Psychopharmacology Incentive Fund, which carried out the assessment of their serum minerals. Results: The BMI of both groups presented similar means, however, the average of %Fat was higher in GQ (p <0.05). As for dietary intake of copper, manganese and zinc, no statistically significant difference between the groups were found. In the other hand, serum levels of copper and manganese were higher and the level of zinc was lower in GQ (p <0.05). Conclusion: Patients with keloids have a higher %Fat, lower serum zinc and higher serum levels of copper and manganese in relation to patients with normotrophyc scars.